Antecedents of Private-Label Brand Purchase Intention: An Experimental Analysis - Ipek, Ilayda; Yilmaz, Cengiz (Routledge Journals, Taylor & Francis Ltd, 2021)
Recent decades have witnessed a growing attention toward private-label brands (PLBs), which also have become of critical importance in emerging markets. Building on this, the main purpose of this empirical research is to investigate the differential influences of individual factors (i.e., socio-demographic aspects, individual differences, and perceptual variables), contextual factors (i.e., distinctive packaging, price promotion, and store image), and attitude toward PLB on PLB purchase intention in an emerging-market context. To serve this purpose, a scenario-based experimental design (N = 351) was used. The findings of the study reveal that prior experience with PLBs, the degree of reliance by consumer extrinsic cues, store image, and attitude toward PLB are precursors of PLB purchase intention, which was found to be inversely related to age, level of purchasing risk, distinctive packaging, and price promotion. This empirical inquiry is expected to provide useful insights into the PLB literature, as it unveils how PLB implications may vary in an emerging-market context.
Ipek, Ilayda/0000-0001-7095-4078; Yilmaz, Cengiz/0000-0002-9383-1457
Keywords: Emerging Country; Experiment; Private-Label Brands; Purchase Intention; Store Brands